The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1590/s0034-89102011000400007
|View full text |Cite
|
Sign up to set email alerts
|

Trabalho, suporte social e lazer protegem idosos da perda funcional: estudo epidoso

Abstract: OBJECTIVE:To identify risk factors for functional capacity loss in elderly people. METHODS:Epidoso (Epidemiology of the Elderly) cohort study with elderly people living in São Paulo (Southeastern Brazil). A total of 326 participants in the fi rst interview (1991)(1992) who were independent or had mild dependence (one or two activities of daily living) were selected. Those who presented functional loss in the second (1994)(1995) or third interviews (1998)(1999) were compared to those who did not present it. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0
39

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(104 citation statements)
references
References 25 publications
(44 reference statements)
5
54
0
39
Order By: Relevance
“…Several factors conventionally associated with functional dependence, in Brazilian and foreign studies, 5,7,8 were also significantly associated with moderate/ severe functional dependence in crude and/or multivariable analysis in the present work. That proves the consistency between data in the present work and literature; and reinforces the association between the independent variable and the outcome in relation to confounding factors.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Several factors conventionally associated with functional dependence, in Brazilian and foreign studies, 5,7,8 were also significantly associated with moderate/ severe functional dependence in crude and/or multivariable analysis in the present work. That proves the consistency between data in the present work and literature; and reinforces the association between the independent variable and the outcome in relation to confounding factors.…”
Section: Discussionsupporting
confidence: 64%
“…Factors conventionally associated to functional dependence in Brazilian and foreign studies include: old age; low education; retirement; cognitive impairment; poor self-rated health; depression and other chronic diseases; hospitalization in the last six months; and infrequent contact with friends. 5,7,8 As contemporary as the general population ageing, the increase in use of digital tools -such as personal computers, selfservice cash (ATM), mobiles, and internet -provides a revolutionary way to social integration, in a process called Digital Inclusion.…”
Section: Introductionmentioning
confidence: 99%
“…A research in the municipality of São Paulo, Brazil, showed that the elderly person with SAH had a 39% more chance in being dependent; the chance rises 59% if they also suffered from osteo-articulation diseases [21]. In fact, these illnesses have triggered a rise in morbi-mortality rates, affect life quality and limit the autonomy of the elderly population with financial impacts on society [22].…”
Section: Discussionmentioning
confidence: 99%
“…Human beings require a daily social conviviality. Salaried work and meeting with kin, friend and neighbors constitute their social relationships [22]. Functional inability has a deep link with not visiting friends and relatives, not meeting with friends at least once a month, and receiving scantly aid from friends [23].…”
Section: Discussionmentioning
confidence: 99%
“…A heterogeneidade do envelhecimento, especialmente entre a população idosa brasileira (Camarano, 2013;Neri, 1993;Pavarini,1997) Estudos referem a importância da manutenção da estimulação cognitiva em idosos saudáveis e em processo de declínio cognitivo. (D'orsi et al, 2011;Fonseca, 2006; 11,12,13 As AAVD, também chamadas de atividades complexas de vida diária, exigem a integridade de múltiplas funções físicas, psicológicas, sociais e cognitivas para sua realização e envolvem a realização de atividades dentro dimensões de participação em atividades sociais, produtivas e de lazer, tais como: habilidades para manter o trabalho, viajar e planejar viagens, participação em grupos ou movimentos comunitários, dirigir, planejar eventos ou jogar. 9,10,11,12 Apesar dos resultados de alguns estudos 11,12 20,21,22,23 A literatura científica sugere que os padrões de atividade e redes neurais relacionadas que são estabelecidos no início da vida possam ser mais importantes para manter a saúde cognitiva na velhice, no sentido de minimizar os efeitos da diminuição da velocidade de processamento cognitivo no envelhecimento.…”
Section: Diferentes Classificações Para As Aavdsunclassified